The Integration of Bloom‟s Digital Taxonomy in EFL Context - ZOUAOUI, Hamza (My University, 2017)
In our days, EFL learning and teaching is facing a massive obstacles, challenges, and hurdles. Bloom‟s Digital taxonomy is more relevant to newer educational theories by combining both the cognitive process and knowledge dimensions. It took a step further by adding multimedia technology to the taxonomy and the associated learning opportunities that emerge from the integration of technology into the learning environment. Whereby different digital tools are aligned to the types of behaviours that can facilitate the process of learning, and where collaboration is a common thread running throughout. Bloom‟s Digital Taxonomy is a measurement tool that takes place in EFL classes in order to provide the best teaching quality for every single learner who seeks to foster his learning process. Indeed, Digital Taxonomies are considered as new educational phenomenon that can rapidly engaged and immerged into higher education. Therefore, in our research project, we have raised some crucial facts about unveiling the effectiveness of Bloom‟s Digital Taxonomy in EFL classes. Practically speaking, gathering students‟ attitudes and teachers‟ perceptions towards the implementation of Bloom‟s Digital Taxonomy in higher education pave the way to create a shift into flipped and digital classrooms rather than traditional ones. In the same phase, this dissertation is divided into three main chapters: the first one sheds the light on the assumptions and pedagogy of Bloom‟s Digital Taxonomy. The second chapter deals with the methodology that structures our investigation and empowers us to bring about clarifications through the use of questionnaires, interview, and an experiment to collect attitudes and responses about the incorporation of Bloom‟s Digital Taxonomy in EFL classrooms. The last chapter highlights the analysis and discussion of the final findings, outcomes, and results that we have deduced from both EFL students and teachers.
Case study: Master EFL Students at Abdelhamid Ibn Badis University, Mostaganem
Keywords: EFL ( English as a foreign language); Learning and teaching; Integration of Bloom‟s Digital Taxonomy; EFL context; Chalenges; Theories